Diseminasi Teknik Artificial Breeding Ikan Air Tawar pada Masyarakat Desa Bukut Kabupaten Gayo Lues - AS, Agus Putra; Gustiana, Cut; Fairus, Fairus; Junita, Afrah (Pendidikan Matematika, FKIP Universitas Mataram, 2025)
Freshwater fish farming is one of the economic potentials that can be developed to improve the welfare of rural communities. Bukut Village has great natural resource potential in the freshwater fisheries sector because it is surrounded by clean and clear rivers. However, there are several main problems that hinder the development of freshwater fish farming in this area, namely: 1) Limited knowledge and technology of freshwater fish hatchery, and 2) Limited availability and quality of freshwater fish seeds. The purpose of this Community Service is to educate the community about artificial breeding techniques through socialization and training or direct practice on how to carry out artificial breeding on freshwater fish to increase the number of freshwater fish seed production and community turnover. The community service method is carried out by dissemination through socialization to increase understanding of good and effective freshwater fish farming, training in artificial breeding techniques from selecting broodstock to hatching eggs, and mentoring. The community service partners are 15 people from the Bukut Village community, Terangun Gayo Lues District. The results of the community service showed that 85% of partners experienced increased knowledge about artificial breeding, 89% of partners understood how to select good broodstock for spawning, 84% of partners understood spawning methods, 83% of partners understood larval maintenance techniques, and 63% of partners' income increased.